(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyses both the form and the content of the novel Leto kada sam naučila da letim (The Summer When I Learned How to Fly) written by Serbian author Jasminka Petrović. Since it deals with literature that is depicting a phase in the development of female identity, it uses the viewpoint of one particular literary genre, female Bildungsroman, and takes into account several of its variants. Rather than firmly placing the analysed novel into strictly or narrowly defined constraints of one particular literary genre, this paper aims to illustrate the novel’s latent potential to be the „interlocutor“ of both the European and the national literary tradition that is related to the exploration of female identity. The essay also attempts to derive conclusions about the current evolutionary stage of the female Bildungsroman, and furthermore, to infer about the genre capacities and limits, given the fact that it has been changing continuously since its emergence, due to its inherent inclusivity.